Ortografi Multigrafik dan Nilai Sosial dalam Wacana Iklan Produk Kecantikan Berbahasa Jepun: Multigraphic Orthography and Social Values in Advertising Discourse of Beauty Products in Japanese Language - Maserah Shabudin dan Idris Aman (Wacana Seni Journal of Arts Discourse, 2013)
In beauty product advertising strategies in Japan, the specialty, uniqueness and advantages of having three main types of orthography, namely kanji, hiragana and katakana, including the Roman Alphabets have resulted in discourse makers taking advantage of these orthographies as creatively and maximally possible in producing an advertising discourse. This article discusses the mechanisms of multigraphic orthography that manifest the values of occidentalisation in the 24 advertising texts studied. From the analysis and interpretation, these occidentalisation values are not only reflected in various forms of foreign loanwords, such as English, French and Italian that are multilingual in form, but also in the "multigraphic" form by taking advantage of four forms of orthography of which each has different graphic characteristics, namely hiragana, katakana, kanji and Roman alphabets. Multilingual benefits in the form of multigraphic orthography in the advertising discourse do not only act as patterns, decorations/ornaments, emphasis and the feel of external image to highlight the differences as a way to attract the public's attention, but also provide prestigious images and atmosphere, symbol of modernity, ease in penetrating the international market and more competitiveness. The presence of foreign loanwords, particularly the English language in the form of katakana and Roman alphabet orthography gives a "fresh" aura and atmosphere, euphemism, more versatility, style, fashion, scientific and futuristic reliability and most importantly, a "complement" to the Japanese writing system itself.